An Analysis of The First Language Acquisition: A Three Years Girl and A Three Years Boy: Language Acquisition - Nurlaela Nurlaela; Yuliana Mangendre (Kodepena Indonesia, 2020)
Language acquisition is a natural process of children in getting language from zero ability become fluency in using language. This research focused on first language acquisition analysis and factors that influence first language (L1) acquisition. It conducted with descriptive qualitative method. The subject of this research is two children in three years old, which is consist of one girl and one boy. The writer took her boy and nephew as the research subject. Observation and documentation in video recording form is technique that used in collecting the data. After the data have been collected and analyzed, it found out (1) Language development of three years girl is faster than three years boy, (2) there are internal factor that affecting first language acquisition of children, and (3) there are external factors that affecting first language acquisition. Keywords : First Language Acquisition, Internal Factors, External Factors